Proteo-metabolomic journey across olive drupe development and maturation. (30th November 2021) - Karagiannis, Evangelos; Michailidis, Michail; Skodra, Christina; Stamatakis, George; Dasenaki, Marilena; Ganopoulos, Ioannis; Samiotaki, Martina; Thomaidis, Nikolaos S.; Molassiotis, Athanassios; Tanou, Georgia
Highlights: Primary metabolism, notably carbohydrates and organic acids, was affected during drupe development. Oleocanthal, rutin, tyrosol and oleuropein were altered across olive drupe development. Three hundred and fifty proteins changed during 'green' to 'black' drupe transition. A scheme of key proteo-metabolomic alterations across olive development is proposed. Abstract: Maturity is one of the most important factors associated with the quality of olive products, however the molecular events underlying olive drupe development remain poorly characterized. Using proteomic and metabolomic approaches, this study investigated the changes in the olive drupes (cv. Chondrolia Chalkidikis) across six developmental stages (S1-S6) that characterize the dynamics of fruit growth and color. Primary metabolites, including carbohydrates and organic acids (i.e., xylose, malic acid), showed significant accumulation in the black maturation stage. Temporal changes in various secondary metabolites (e.g., oleuropein, oleacin and tyrosol) were also observed. Proteins involved in oxidation–reduction (i.e., LOX1/5), carbohydrate metabolism (i.e., GLUA, PG) and photosynthesis (i.e., chlorophyll a -b binding proteins) significantly altered in the turning black compared to the green mature stage. By providing the first proteometabolomic study of olive drupe development, this investigation offers a novel framework for further studies on this economically relevant crop.